2020
DOI: 10.1094/pdis-03-19-0572-re
|View full text |Cite
|
Sign up to set email alerts
|

Specific Detection and Identification of Fusarium graminearum Sensu Stricto Using a PCR-RFLP Tool and Specific Primers Targeting the Translational Elongation Factor 1α Gene

Abstract: Fusarium graminearum is a toxigenic plant pathogen that causes Fusarium head blight (FHB) disease on cereal crops. It has recently shown to have cross-pathogenicity on noncereals (i.e., Fusarium root rot [FRR] on soybean) in Canada and elsewhere. Specific detection and differentiation of this potent toxigenic, trichothecene-producing pathogen among other closely related species is extremely important for disease control and mycotoxin monitoring. Here, we designed a PCR restriction fragment length polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 83 publications
0
7
0
1
Order By: Relevance
“…The unidentified strains from PR state were assayed using the Fg16‐F/R primers, which allow differentiation between F . graminearum (<500 bp) and Fusarium meridionale (>500 bp) according to the band product size (Hafez et al, 2020; Nicholson et al, 1998). Primer sequences and product size can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The unidentified strains from PR state were assayed using the Fg16‐F/R primers, which allow differentiation between F . graminearum (<500 bp) and Fusarium meridionale (>500 bp) according to the band product size (Hafez et al, 2020; Nicholson et al, 1998). Primer sequences and product size can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Tri5 , Tri6 , EF1-A and β-Actin genes were used for F. graminearum detection and relative quantification based on qPCR [ 46 , 47 , 48 , 49 ], in order to confirm the results obtained with the plating technique, which indicated that the PAW bubble treatment did not have any effect on F. graminearum infection or growth. DON biosynthesis is governed by fifteen genes that are present over three chromosomes [ 50 ] and an acidic pH of environment encourages DON biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Four F. graminearum -specific genes were targeted. The full sequence of the genes, including Trichothecene biosynthesis transcription regulator ( Tri6 , GenBank: AB017495.1), Terpene cyclase trichodiene synthase ( Tri5 ; GenBank: KJ677974.1) [ 46 ], Elongation factor 1-alpha ( EF1 A ; GenBank: KX084040.1) [ 47 ], and Actin (NCBI Reference Sequence: XM_011328784.1) [ 48 ] were retrieved from the NCBI sequence database. Gene-specific primers ( Table 6 ) were designed using Primer Express 3.0.1 (Applied Biosystems, Mississauga, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there are no orthologous copies of TEF-1 α in this genus, making this locus a better candidate for distinguishing phylogenetic relationships ( Amarasinghe et al, 2019 ). Therefore, classification and identification of Fusarium species based on TEF-1 α gene sequences has become the most common method ( Mirete et al, 2004 ; Hafez et al, 2020 ). Geiser et al (2004) established a Fusarium database based on the partial sequence of the TEF-1 α gene, which allows researchers to easily identify species under Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%